2013
DOI: 10.1063/1.4818681
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental identification of the out-of-plane phonon mode of a few layered graphene from individual Au nanoparticle-Au film junctions

Abstract: Detection of organic vapors by graphene films functionalized with metallic nanoparticles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Optical characterization of CVD-MG by upright-type Raman spectroscopy is extensively used as a conventional method to understand the degree of doping [35], number of layers [36], and the influence of mechanical strain [6,34,35,37] predominantly employing in-plane phonon vibrations. Park and colleagues readily recognized the z-directional out-of-plane phonon vibrational modes, such as the RBLM and transverse nano-scroll-type defect modes of CVD-MG at each of the Au NP/Au film junctions via the SERS signal obtained using linearly polarized HeNe laser (633 nm) irradiation [20,21,25,26]. Generally, a 633 nm laser beam is utilized as the excitation source since it closely matches the localized surface plasmon (LSP) resonance of Au NPs and the coupled resonance surface plasmon polariton (SPP) of the Au NP-Au film junction system [18][19][20][21][22][23][24][25][26].…”
Section: Optical Characterization Of Cvd-mg On Cu and Sio 2 /Si Substratementioning
confidence: 99%
See 4 more Smart Citations
“…Optical characterization of CVD-MG by upright-type Raman spectroscopy is extensively used as a conventional method to understand the degree of doping [35], number of layers [36], and the influence of mechanical strain [6,34,35,37] predominantly employing in-plane phonon vibrations. Park and colleagues readily recognized the z-directional out-of-plane phonon vibrational modes, such as the RBLM and transverse nano-scroll-type defect modes of CVD-MG at each of the Au NP/Au film junctions via the SERS signal obtained using linearly polarized HeNe laser (633 nm) irradiation [20,21,25,26]. Generally, a 633 nm laser beam is utilized as the excitation source since it closely matches the localized surface plasmon (LSP) resonance of Au NPs and the coupled resonance surface plasmon polariton (SPP) of the Au NP-Au film junction system [18][19][20][21][22][23][24][25][26].…”
Section: Optical Characterization Of Cvd-mg On Cu and Sio 2 /Si Substratementioning
confidence: 99%
“…Park and colleagues readily recognized the z-directional out-of-plane phonon vibrational modes, such as the RBLM and transverse nano-scroll-type defect modes of CVD-MG at each of the Au NP/Au film junctions via the SERS signal obtained using linearly polarized HeNe laser (633 nm) irradiation [20,21,25,26]. Generally, a 633 nm laser beam is utilized as the excitation source since it closely matches the localized surface plasmon (LSP) resonance of Au NPs and the coupled resonance surface plasmon polariton (SPP) of the Au NP-Au film junction system [18][19][20][21][22][23][24][25][26]. Based on these studies, the un-polarized SERS signals identified along the z-axis were attributed to the xy-plane axially symmetric SERS signal distribution from a z-directional dipole emitter (corresponding to the Au NP-Au film coupling orientation).…”
Section: Optical Characterization Of Cvd-mg On Cu and Sio 2 /Si Substratementioning
confidence: 99%
See 3 more Smart Citations